Reviving production and business by brand refresh, rebrand: economic benefits and some key points to note - Khong Quoc Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
In the “new normal” situation of the COVID-19 pandemic, the revival of production and business is one of the biggest challenges for businesses. This is also the right time for these enterprises to review priority areas, find differences, reinvent ourselves and new ways of operating, new directions in line with market needs for the purpose of a stronger development and existence. As trademarks is considered as one of the effective tools to promote commercial activities, such revival is usually starts with a brand refresh and rebrand. For the sake of efficiency, enterprises need to distinguish the difference between them and know well about the feasibility of each this option. In addition , they should exploit industrial property information effectively and always take note of financial and legal risks. Code: 22032101